Griscelli Syndrome Type 2 Sine Albinism: Unraveling Differential RAB27A Effector Engagement - Ohishi, Yuta; Ammann, Sandra; Ziaee, Vahid; Strege, Katharina; Groß, Miriam; Amos, Carla Vazquez; Shahrooei, Mohammad; Ashournia, Parisa; Razaghian, Anahita; Griffiths, Gillian M.; Ehl, Stephan; Fukuda, Mitsunori; et al. (Frontiers in Immunology, 2020)
Griscelli syndrome type 2 (GS-2) is an inborn error of immunity characterized by partial albinism and episodes of hemophagocytic lymphohistiocytosis (HLH). It is caused by RAB27A mutations that encode RAB27A, a member of the Rab GTPase family. RAB27A is expressed in many tissues and regulates vesicular transport and organelle dynamics. Occasionally, GS-2 patients with RAB27A mutation display normal pigmentation. The study of such variants provides the opportunity to map distinct binding sites for tissue-specific effectors on RAB27A. Here we present a new case of GS-2 with no albinism (GS-2 sine albinism) caused by a novel missense mutation (Val143Ala) in the RAB27A and characterize its functional cellular consequences. Using pertinent animal cell lines, the Val143Ala mutation impairs both the RAB27A–SLP2-A interaction and RAB27A–MUNC13-4 interaction, but it does not affect the RAB27A–melanophilin (MLPH)/SLAC2-A interaction that is crucial for skin and hair pigmentation. We conclude that disruption of the RAB27A–MUNC13-4 interaction in cytotoxic lymphocytes leads to the HLH predisposition of the GS-2 patient with the Val143Ala mutation. Finally, we include a review of GS-2 sine albinism cases reported in the literature, summarizing their genetic and clinical characteristics.